1996
DOI: 10.1007/bf01426622
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of 2p 4(3 P)nl(l=s, d) Rydberg spectra of the fluorine isoelectronic sequence

Abstract: Abstract.The basic structure parameters of 2p4(3p)ns and 2p4(3p)nd (J = 1/2, 3/2 and 5/2) Rydberg spectra for the fluorine isoelectronic sequence from FI to NiXX, as functions of effective nuclear charge, are calculated by using the eigenchannel quantum-defect theory. The results can be interpreted in terms of the variations of electrostatic and spin-orbit interactions along the sequence. A vast amount of basic atomic data can be obtained with these parameters as input. Some numerical examples are given, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Figure S10 demonstrates that the absorption spectra were altered, suggesting a definite interaction between the N-CQDs and Cu 2+ to form the complex. In addition, FT-IR spectra (Figure 4A) showed that the band at 3456 cm −1 became broader and a new band at 1751 cm −1 emerged as N-CQDs/Cu aggregate forms, 33 further corroborating with EDX (Figure 4B), XPS (Figure 4C−G), TEM (Figure S11), and DLS results (Figure 5A). The XPS spectra of the N-CQDs/Cu complex distinctly reveal the presence of Cu 2p 1/2 and Cu 2p 3/2 alongside C, N, and O (Figure 4C−G).…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…Figure S10 demonstrates that the absorption spectra were altered, suggesting a definite interaction between the N-CQDs and Cu 2+ to form the complex. In addition, FT-IR spectra (Figure 4A) showed that the band at 3456 cm −1 became broader and a new band at 1751 cm −1 emerged as N-CQDs/Cu aggregate forms, 33 further corroborating with EDX (Figure 4B), XPS (Figure 4C−G), TEM (Figure S11), and DLS results (Figure 5A). The XPS spectra of the N-CQDs/Cu complex distinctly reveal the presence of Cu 2p 1/2 and Cu 2p 3/2 alongside C, N, and O (Figure 4C−G).…”
Section: ■ Results and Discussionsupporting
confidence: 63%